Analisa Reaksi Pasar Modal terhadap Perang Rusia-Ukraina pada Bursa Efek Indonesia - Ossi Ferli; Enny Haryanti; Zahra Muthia Rahmawati; Nurlita Dewi (Journal of Management and Bussines (JOMB), 2024)
This research aims to analyze the impact of the Indonesian capital market's reaction to the announcement of Russia's invasion of Ukraine on February 24 2022. Special focus is given to companies in the food industry sector that use wheat as the main raw material. Six companies listed on the Indonesian Stock Exchange that rely on wheat were the subject of analysis. The research method uses an event study approach by calculating cumulative abnormal returns and average trading volume activity in the time period February 2022-March 2022. The research results show that there are no significant differences in the calculated variables between the periods before and after the announcement of the Russian-Ukrainian invasion. The implication is that the Indonesian capital market, especially companies in the food industry sector, did not experience a significant impact due to this incident. This research contributes to understanding the capital market response to geopolitical events and its relevance to the food industry sector in Indonesia. In conclusion, the resilience of the Indonesian capital market to certain foreign events and emphasizes the importance of diversifying raw materials in the food industry to reduce potential external risks. Keywords: Reaction Analysis, Indonesian Stock Exchange, Geopolitical Impact, Capital Markets, Russian-Ukrainian War